HUBUNGAN POLA ASUH ORANG TUA DENGAN PRESTASI BELAJAR SISWA-SISWI SDN TURIPINGGIR 1 DI MASA PANDEMI COVID-19 DI DESA TURIPINGGIR KECAMATAN MEGALUH KABUPATEN JOMBANG - Yunita Sari, Ayu; Puspita, Sylvie; Melliya Sari, Gevi (PRIMA WIYATA HEALTH, 2022)
Parenting patterns of parents have a big influence on how children see themselves and their emvironment so that it affects learning achievement at school, especially for elementary school chiIdren. This study ains to analyze the relationship between parenting style and learning achievement of SDN Turipinggir 1 students during the Covid-19 pandemic in Turipinggir Village, Megaluh District, Jombang Regency. PThis study uses a case controI design with a retrospective approch. The sampIe in this study were 40 respondens with the Total Samplimg techniqe. Data collection using a questionnaireand student report cards while the data analysis using the test Spearman rank's. On research This shows that most of the studeents received democratic parenting from their parents as many as 31 respondents (77,5%).The resuIts of the Spearman Ranks test obtaned a correlation coefficient of 0,914 which shows the Ievel of closenees of the reIationship between the parenting style variable and students' learning achievement because it is located between 0.800 – 1,000 the relationship is very strong while the level of probability of error 0,000, whih is smalIer than the condition p < 0,05, indicating thad H0 is reject and H1 is acepted. Parents who always express affection and control emotions are good parenting styles. When children feel cared for, confidentto develop talents, be expressive, creative so that their learning achievement is optimal.